Teaching economics in troubled times : theory and practice for secondary social studies - Schug, Mark C.; Wood, William C., 1952- (Routledge, 2011)
Teaching Economics in a Time of Unprecedented Change is a one-stop collection that helps pre- and in-service social studies teachers to foster an understanding of classic content as well as recent economic developments.